The solution to the expression 3 * 9 + 10 * 36/6 is 87
From the question, we have the following parameters that can be used in our computation:
3 * 9 + 10 * 36/6
Evaluate all the products in the expression
so, we have the following representation
3 * 9 + 10 * 36/6 = 27 + 360/6
Evaluate all the quotients in the expression
so, we have the following representation
3 * 9 + 10 * 36/6 = 27 + 60
Lastly, we have
3 * 9 + 10 * 36/6 = 87
Hence, the solution is 87
Read more about expressions at
#SPJ6
Answer:
87
Step-by-step explanation:
3x9+10x36/6
multiply 3x9 and divided 36/6
27+10x6
27+60
87
4b + 5 = 1 + 5b
b=
Answer:
b=4
Step-by-step explanation:
4b + 5 = 1 + 5b
Subtract 4b from each side
4b-4b + 5 = 1 + 5b-4b
5 =1+b
Subtract 1 from each side
5-1 = 1-1+b
4 =b
Steps to solve:
4b + 5 = 1 + 5b
~Subtract 5b to both sides
4b - 5b + 5 = 1 + 5b - 5b
~Simplify
-b + 5 = 1
~Subtract 5 to both sides
-b + 5 - 5 = 1 - 5
~Simplify
-b = -4
~Divide -1 to both sides
-b/-1 = -4/-1
~Simplify
b = 4
Best of Luck!
No idea how to figure this out ive never done it (at least ive not done it yet in my near 4yrs of hs(not American hs, British(we start it at 11-12)
Answer:
21 and 3
Step-by-step explanation:
Let's call the small number and the larger number .
According to the problem:
And when you substract the smaller number from the larger number you get 18:
substituting the first equation in the second one:
the larger number is 21.
Using the first equation to find :
the smaller number is 3.
Answer:
Subtract 4
Step-by-step explanation:
-3 - 4 = -7
-7 - 4 = -11
-11 - 4 = -15